Tools for the metal processing of the Alakul population of the foreststeppe Tobol River basin - Kostomarova Yu.V.; Sechko E.A. (Вестник археологии, антропологии и этнографии, 2023)
The paper presents the results of the study of a tool complex associated with metalworking from the sites of the Alakul Culture of the forest-steppe Tobol River basin — the settlements of Kamyshnoe 1 and 2, Uk 3, Nizhneingalskoe 3, and Zolotoe 1. The Alakul antiquities, in general, date to 1900–1450 BC. The purpose of this work is the consolidation and clarification of information on the metalworking of the Alakul population of the forest-steppe Tobol basin. For this purpose, collections of trade tools of the aforementioned Alakul settlements were revisited; the tools used in the production in question were identified; the signs of their wear, documented by a series of microphotographs, were characterised; and groups of the tools were identified according to their functional feature. The main research method was experimental-traceological. It implies, firstly, the study of traces of wear, their mutual occurrence and specifics of the location on the tools; secondly, the comparison of the obtained characteristics with experimental data. In the work, theoretical and experiential concepts of the methodology and classification schemes developed by S.A. Semenov, G.F. Korobkova, and V.V. Kileynikov were employed. To verify the traces of wear on archaeological tools, experimental reference samples of the tools were used, obtained during many years of work and stored in the Tyumen Scientific Centre SB RAS. As analogies, published results of the experiments and experimental and traceological studies of similar tools from territorially close Bronze Age sites were used. As the result, forging tools (hammers for cold and hot forging of castings, smoothers) and abrasive tools were identified; their technological characteristics and distinctive signs of wear marks were clarified. A set of tools in one quantity or another was recorded at each of the studied sites; therefore, the blacksmith production was quite developed also on the periphery of the Alakul Culture. Additional arguments were obtained in favour of the hypothesis that the ore processing was taking place in the immediate vicinity of its sources, and the metal could have been supplied to the remote villages already in a ‘finished’ form; there, the products were cast, forged, and finished. Analogies to the studied tools are known from the earlier Petrovka and Sintashta complexes of the Southern Trans-Urals. Thus, we can talk about common patterns in the manufacture and use of metalworking tools during the Bronze Age in the Trans-Urals territory.